Does Socioeconomic Status Influence Achievement? An analysis of the Performance of Kosovar Students on the 2015 and 2018 PISA Assessment - Shala, Arif; Grajcevci, Albulene; Latifi, Fadil (Revija za elementarno izobraževanje, 2021)
Socioeconomic status has long been considered an influential factor in student achievement. Similar to existing literature, results of this analysis reveal that socioeconomic status influenced student achievement in the 2015 and 2018 PISA assessments. However, the achievement gap between categories widened between 2015 and 2018. Results reveal that home possessions, school location, parental education played a role in achievement. Furthermore, students who attended private schools outperformed students in public schools, a gap that widened considerably between assessments. Results of the current analysis reveal the importance of socioeconomic factors in achievement and, the need for policy builders to mitigate this impact.